EMPLOYEE PERFORMANCE ROLE: COMMUNICATION AND WORK DISCIPLINE - Dani Iskandar (CERED Indonesia Institute, 2021)
The purpose of this study was to determine the effect of communication and work discipline on employee performance at PDAM Tirtanadi, North Sumatra. The population of this study was taken from all employees of PDAM Tirtanadi in North Sumatra, and a sample of 63 employees using the Slobin formula. The data acquisition technique using a questionnaire has been tested for validity and reliability, as well as library research. The data analysis technique used classical hypothesis test, multiple regression, F test, t test, and coefficient of determination. Based on the results of the simultaneous test, it was found that the value of Fcount (8.400) > Ftable (3.150), and sig (.000a) < 5% (0.05). Simultaneously, communication and work discipline have a significant effect on the performance of PDAM Tirtanadi employees, North Sumatra Province. Based on the t-test of the communication variable, the tcount value is 2.230 > ttable 2000 with sig. 0.029. This shows that there is an effect of communication on the performance of PDAM Tirtanadi employees, North Sumatra Province. Variable work discipline tcount 2,976 > ttable 2,000 with sig. 0.004. shows that work discipline has a significant effect on the performance of PDAM Tirtanadi employees, North Sumatra Province. The value of the coefficient of determination is 0.219. This shows that 2.19% of the communication and work discipline variables explain the performance of PDAM Tirtanadi employees, North Sumatra Province. While 78.1% is influenced by other variables not examined. shows that work discipline has a significant effect on the performance of PDAM Tirtanadi employees, North Sumatra Province. The value of the coefficient of determination is 0.219. This shows that 2.19% of the communication and work discipline variables explain the performance of PDAM Tirtanadi employees, North Sumatra Province. While 78.1% is influenced by other variables not examined. shows that work discipline has a significant effect on the performance of PDAM Tirtanadi employees, North Sumatra Province. The value of the coefficient of determination is 0.219. This shows that 2.19% of the communication and work discipline variables explain the performance of PDAM Tirtanadi employees, North Sumatra Province. While 78.1% is influenced by other variables not examined.